Revitalizing Government Internal Auditor Apparatus in the Era of Industry 4.0 - Basri, Muh Ridwan (Universitas Bina Sarana Informatika, 2024)
The purpose of this paper is to propose a transformation strategy which is the focus of the Government Internal Supervisory Apparatus (APIP) on the impact of Industry 4.0 on the internal audit function and the development of an improvement plan for the Internal Auditor SPIP level . can be applied to address audit challenges in the Industry 4.0 era. Due to the impact of Industry 4.0 on audit activities, APIP is required to be able and quickly adapt to technological advances. The adoption of Industry 4.0 technology positions APIP as an activity analyst who can identify errors in business processes and devise solutions to fix them. As a consequence, an APIP transformation strategy is needed to face the challenges of Industry 4.0. The author suggests that the APIP transformation strategy to increase the SPIP level must include: (1) the use of data collection equipment, such as sensors and software, to collect data; (2) inclusion of characteristics that characterize APIP's ability to complete audit tasks, including cognitive abilities, problem solving abilities, communication skills, internal control systems, and agility; and (3) applying a professional, millennial, innovative approach that prioritizes integrity, objectivity and professionalism while still embracing the possibility of failure.